Proteomic investigations on the mechanism of neurotoxicity in low-dose chronic methylmercury intake - Kong, H.K.; Lo, >S.C.L. (Progress in Nutrition, 2011)
Summary Contamination of seafood and especially fish with methylmercury is becoming a global issue. We fed rats with a low dose methylmercury (40 ug/kg body weight/day) for 3 months in order to see if the protein expressions in their brains were affected. With proteomic technologies, we found that the expression of about 100 proteins in the somatic sensory cortex was altered. A significant portion of these proteins are enzymes of the metabolic pathways. This finding is in line with the hypothesis that methylmercury accumulation in the brain caused decreased energy supply which eventually impaired ability for auto-repair in the brain. Analisi proteomica sul meccanismo di neurotossicità dell’assunzione cronica in basse dosi di metilmercurio Riassunto La contaminazione dei prodotti ittici e soprattutto del pesce con metilmercurio sta diventando un problema globale. Abbiamo nutrito ratti con basse dosi di metilmercurio (40 ug/kg di peso corporeo/die) per 3 mesi per analizzarne l’influenza sull’espressione proteica ​​nei loro cervelli. Con tecnologie proteomiche, abbiamo scoperto che era stata alterata l’espressione di circa 100 proteine ​​nella corteccia sensoriale somatica. Una significativa porzione di queste proteine ​​sono enzimi di pathways metabolici. Questo risultato è in linea con l’ipotesi che l’accumulo di metilmercurio nel cervello causi una diminuzione dell’approvvigionamento di energia che col tempo ridurrebbe la sua capacità di auto-riparazione.